Analysis of a travertine system controlled by the transpressional activity of the Alhama de Murcia fault: The Carraclaca site, eastern Betic Cordillera, Spain - Canora, Carolina; Cuevas Rodríguez, Jaime; Martínez Díaz, José Jesús; Garralón, Antonio (Frontiers in Earth Science, 2023)
Continental carbonates, such as travertines and tufas, formed from CO2-rich groundwater degassing as it emerges at the Earth’s surface, are often associated with major crustal-scale faults. The Carraclaca site, in the Lorca-Totana section of the Alhama de Murcia Fault, presents a complex geomorphological landscape controlled by active tectonics. The geology here records the interaction between Quaternary alluvial fans, travertines, and a pop-up structure developed in a transpressional section of the fault. The Alhama de Murcia Fault is an 80 km long left-lateral strike-slip fault that is one of the main seismogenic structures in the Iberian Peninsula. In this work, we examined the relation between travertine precipitation in the Carraclaca site and the tectonic activity of this fault zone through morphological and geochemical studies. The δ13C and δ18O isotopic signals indicate that the carbonate deposits are hydrothermal. In addition, the 87Sr/86Sr ratios in the samples suggest subsurface fluid interaction with the Miocene sediments and the Alpujárride basement, located below the alluvial deposits. The tectonic activity in the Alhama de Murcia Fault generates the opening of the hydrothermal circulation in the crust every time a seismic event occurs. The deep waters rise and reach the surface interacting with the meteoric waters, resulting in the travertine formation. Therefore, the Carraclaca carbonate deposits study can inform us about the seismogenic cycle of the fault in the Lorca-Totana section.